ON DYNAMICS OF LEGISLATIVE WORK AND ITS EFFECTS - Nikolić, Dušan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Through a short comparative analysis, the author showed how much the speed of legislative work can influence the quality of normative solutions, and their effects in legal practice. Special attention was paid to the Austrian civil code (Allgemeines bürgerliches Gesetzbuch – АBGB, ACC), of year 1811, which succeeded in resisting the challenges of time for two centuries. A number of factors influenced its longevity. First of all, prior to adoption of the law, a long lasting and well designed work, which has been described in greater detail in this article, was done. The Code was written gradually, with lots of recalculations, checks and public debates. In legal literature, it is often written about a unique lawmaking experiment, which Austrian authorities made by implementing the Code in one part of the state territory. The Code was written for feudal order, but according to principles of natural law. This second thing has, in addition to widely formulated and flexible legal norms, left enough space for extensive interpretation of outdated rules, and filling in the legal lacunas, whose number was increasing as the time passed. Courts often used this opportunity in a creative manner, contributing to survival of the Code. Many additions and changes were made to the Code, but there were few of those who thought that it should be changed by a new one Code. Austrians are preparing a more detailed revision of the ACC, which will allow modernization of the national law and it’s synchronization with trends in current European law, but on the other hand, to preserve the two century old legal heritage. In contrast, the Serbian civil code of 1844. emerged from different social and economic conditions. It was written in a relatively short period of time, with the Austrian code as a model. The opinion that the legislator contributed to the rapid decadence of family clans (porodična zadruga) and along with it the economic weakening of society as a whole, by his inappropriate adoptions of normative solutions from foreign law, is predominant. Similar processes are taking place today. Supranational law of the European Union is being shaped progressively, in a long time period, which is measured in decades. On the other hand, countries which are candidates for membership in the EU are required to adopt hundreds of laws and other regulations, in accordance with European legal standards, in very short time.